2017
DOI: 10.17116/terarkh201789538-45
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the serum concentrations of adhesion molecules and vascular endothelial growth factor in active ankylosing spondylitis patients taking amtolmetin guacil: Results of a 56-week prospective ореn-label controlled observational study

Abstract: Elevated concentrations of adhesion molecules have been found in AS patients compared with healthy individuals. The study has demonstrated that AMG treatment is efficient in treating patients with AS. NSAID/AMG treatment is associated with lower concentrations of adhesion molecules. Decreased CRP levels serve as predictors for reduced concentration of adhesion molecules. The level of VEGF-A at baseline did not differ from that in healthy subjects, but was decreased during treatment with NSAIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…One of these mechanisms is associated with the strong stimulatory effect of oxidised lipoproteins on the expression of cytokine-induced vascular adhesion molecules (VCAM-1), which mechanically links inflammation to the atherogenic process. 17, 18 In fact, Gaydukova et al 19 reported that the plasma levels of vascular adhesion molecules were higher in AS patients, compared to healthy control subjects. Another mechanism is related to the vascular endothelium being a target of tumour necrosis factor alpha (TNF-α), which has a major role in the pathogenesis of chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…One of these mechanisms is associated with the strong stimulatory effect of oxidised lipoproteins on the expression of cytokine-induced vascular adhesion molecules (VCAM-1), which mechanically links inflammation to the atherogenic process. 17, 18 In fact, Gaydukova et al 19 reported that the plasma levels of vascular adhesion molecules were higher in AS patients, compared to healthy control subjects. Another mechanism is related to the vascular endothelium being a target of tumour necrosis factor alpha (TNF-α), which has a major role in the pathogenesis of chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%